2017
DOI: 10.1038/s41598-017-07314-5
|View full text |Cite
|
Sign up to set email alerts
|

Uracil Accumulation and Mutagenesis Dominated by Cytosine Deamination in CpG Dinucleotides in Mice Lacking UNG and SMUG1

Abstract: Both a DNA lesion and an intermediate for antibody maturation, uracil is primarily processed by base excision repair (BER), either initiated by uracil-DNA glycosylase (UNG) or by single-strand selective monofunctional uracil DNA glycosylase (SMUG1). The relative in vivo contributions of each glycosylase remain elusive. To assess the impact of SMUG1 deficiency, we measured uracil and 5-hydroxymethyluracil, another SMUG1 substrate, in Smug1 −/− mice. We found that 5-hydroxymethyluracil accumulated in Smug1 −/− t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…These two limitations relate to, on the one hand, the set of enzymes capable of recognizing and cleaving uracil from DNA, and on the other hand, to the set of proteins required for the short-patch versus long-patch BER routes. Uracil-DNA glycosylases in diverse organisms include at least four enzyme families (UNG, TDG, SMUG, MBD4) [35,36]. The diversity in these enzymes defines their specific roles and different substrate specificities and underlies the high significance of uracil removal from DNA.…”
Section: Resultsmentioning
confidence: 99%
“…These two limitations relate to, on the one hand, the set of enzymes capable of recognizing and cleaving uracil from DNA, and on the other hand, to the set of proteins required for the short-patch versus long-patch BER routes. Uracil-DNA glycosylases in diverse organisms include at least four enzyme families (UNG, TDG, SMUG, MBD4) [35,36]. The diversity in these enzymes defines their specific roles and different substrate specificities and underlies the high significance of uracil removal from DNA.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the function of SMUG1 in Terc biogenesis contributes to the apparently stronger telomere phenotype in Smug1 À/À mice, but although SMUG1 binds Terc in MEFs ( Figure S1F), Smug1 À/À MEFs did not show consistently reduced Terc levels ( Figure S1G). Therefore, the telomere maintenance defects in MEFs appear to be mainly caused by the loss of SMUG1-dependent BER (Alsøe et al, 2017). Measurements of telomere fragility (Figures 2D, 2E, and S1D) indicated impaired replication of the C-rich telomere strand, which would be expected to contain more uracil lesions.…”
Section: Discussionmentioning
confidence: 96%
“…We previously observed that overexpression of a SMUG1 mutant unable to interact with DKC1 (E29R/E33R) affected DKC1 localization in HeLa cells (Jobert et al, 2013). To confirm that disruption of the SMUG1/DKC1 interaction surface perturbs proper localization of DKC1, we repeated these experiments in Smug1 À/À mouse embryonic fibroblasts (MEFs) (Alsøe et al, 2017). To exclude any bias originating from possible small differences in cell-cycle distribution, we scored the ring-shaped structures formed by DKC1 (DKC1 circles) during S phase (Lee et al, 2014).…”
Section: Smug1 Influences Dkc1 Localizationmentioning
confidence: 99%
See 2 more Smart Citations